Stateless within the States: American Homeland Security after 9/11 and Francis Lawrence’s I Am Legend - Eunju Hwang (European Journal of American Studies)
This essay attempts to place I Am Legend (2007) in the context of American nationalism and aggressive enforcement of the immigration laws after 9/11. The apocalyptic world of I Am Legend reflects the post-9/11 American society that is driven by the urge to make America “one nation” and haunted by the fear of people who might harm the “unity.” The film tries to draw a clear boundary between “us” and “them” by completely othering the infected, but in the context of American homeland security after 9/11, it becomes a complex issue to decide where to draw the line. The shifty boundary between “us” and “them” reflects the post-9/11 American dilemma: the United States has to close its border while maintaining its identity as a nation of immigrants. This essay also discusses how geographical markers, instead of racial markers, are utilized to symbolize the infected as the stateless people within the United States.